Psychosis after vagus nerve stimulation therapy. Issue 5 (September 2014) - Chen, Wei‐Ling; Lin, Chin‐Chien; Chan, Chin‐Hong
Abstract A 24‐year‐old man developed psychosis after improvement of epilepsy with vagus nerve stimulation treatment. He had a similar response when seizures were controlled by anticonvulsion agents. Psychosis was relieved with withdrawal of antiseizure treatment, but seizures then recurred.